Pemanfaatan Arang Sekam Padi dan Pupuk Organik Cair (POC) Bonggol Pisang Terhadap Pertumbuhan Vegetatif Tomat (Lycopersicum esculantum Miil) - Muhammad Firdaus; Antar Sofyan; Jumar Jumar (Agroekotek View, 2021)
Rice husks are waste from rice mills which are still rarely used by the community even though it is very potential to be used, especially in the agricultural sector, as a soil amendment, planting medium, compost and other agricultural materials. Just like rice husks, banana weevils are also agricultural waste which often only becomes waste without being used by the community even though it has many benefits if used especially in agriculture, banana weevils contain many microorganisms and substances that can be used in agriculture. Tomato (Lycopersicum esculantum Mill) is one of the horticultural crops that many farmers are interested in cultivating because it has high economic value and is in great demand by the community. This study aims to determine the response of tomato growth to several types of growing media and to determine the response of tomato growth to several doses of liquid organic fertilizer.